ANALISIS PROSES PEMBELAJARAN MATEMATIKA ABK HIPERAKTIF DI KELAS II INKLUSIF - Marlina, Rosy; Budiyono, Budiyono; Usodo, Budi (Universitas Sebelas Maret, 2018)
Abstract : Mathematical difficulties in children with special needs (ABK) hyperactivity become a challenge for mathematics teachers in learning. The existence of curriculum targets and demands must be adjusted to the conditions of hyperactive ABK who have difficulties in terms of concentration. The purpose of this study was to describe the strategies and constraints of teachers in teaching mathematics to hyperactive ABK in inclusive class II, as well as their suitability with the conditions and needs of hyperactive ABK. This research is a qualitative field research research with purposive sampling. Samples from this study are classroom teachers who teach mathematics, Special Guidance Teachers (GPK) shadow and hyperactive ABK. The instruments used are observation, documentation and interviews. The results showed that mathematics learning for hyperactive ABK was accompanied by GPK Shadow with the approach of Individual Learning Program (PPI) in inclusive classes allowing hyperactive ABK to focus more on learning and feel comfortable because they could be with their classmates. The curriculum model used is a modified regular curriculum, including modification of goals, materials, processes and evaluations.Keywords:Mathematics Learning, Hyperactive Abk, Inclusive Class.